ART-BASED INTERVENTIONS FOR MENTAL HEALTH AND EMOTIONAL WELL-BEING - Ghunkikar, Prashant Vasant; Sule , Bipin; Shrivastava, Amit Kumar; Dr. L. Malathi; Prasad, Durga; Kariveliparambil, Ashifa (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Mental illnesses like anxiety, depression, and emotional distresses have become a common issue among the various age groups. The old treatment methods such as psychotherapy and medication have been shown to be effective but tend to lack in meeting the needs of creative and an emotional expression of patients. As a means of healing, art-based interventions have developed as a form of complementary therapy, where the participants are able to express their feelings, alleviate mental stress and elevate their emotions through artistic endeavours. The study examines the importance of art-based interventions in mental health care and suggests a systematic model that includes artistic activities with psychological testing and electronic surveillance monitoring instruments. The study examines current methods of art-therapy, including the visual arts therapy, music therapy, dance/movement therapy, and the expressive writing. They are compared and analyzed based on their effectiveness in terms of emotional expression, accessibility, therapeutic engagement and outcome measurement. On the basis of limitations identified, the new hybrid system is offered with the combination of digital platforms, guided activities, emotional tracking and therapist feedback to increase the results of therapy. The suggested structure allows a systematic provision of intervention and maintains the creative freedom. The anticipated benefits are the enhanced emotional control, enhanced patient involvement, and improved observation of therapeutic progress. In the study, the authors present the significance of incorporating artistic activities into the system of mental health support and propose the potential directions of future research that involve the use of AI-assisted analysis of emotions and digital art therapy platforms.